MESH DEPENDENCY STUDY USING NUMERICAL MODELING FOR PILLAR STABILITY ANALYSIS BASED ON THE HOEK-BROWN CRITERIA - Alif Lam Ha, Abda
The underground mining sector poses a high risk of work-related accidents, necessitating the implementation of effective risk control measures to prevent such incidents. One crucial aspect of risk control in mining operations is the design of stable pillars. This research employs the finite element method within the RS2 software to model underground mining pillars. The modeling process incorporates the Hoek-Brown criterion, with variations in the ratio of horizontal stress (0.5, 1, and 2) as the field stress parameter. Furthermore, the shape of the elements and the number of nodes surrounding the pillar are systematically varied from 50 to 500, with increments of 50. The rock material under investigation exhibits strain softening behavior. The safety factor and strength factor of the pillars are influenced by the number of nodes surrounding the pillar. The relationship between the safety factor, strength factor, and mesh displays non-continuous fluctuations as the number of elements and nodes increases. However, a general tendency is observed, indicating a decline in both the safety factor and strength factor as the number of elements and nodes increases. Notably, in the case of a horizontal stress ratio of 0.5, the strength factor demonstrates a tendency to stabilize after reaching a sufficiently large number of nodes. Consequently, it can be inferred that, in the context of this modeling study, an increase in the number of elements and nodes generally leads to a decrease in the safety factor and strength factor. However, the behavior of the strength factor exhibits variations depending on the value of the horizontal stress ratio employed, wherein the strength factor tends to stabilize after a considerable number of nodes have been utilized when a ratio of 0.5 is considered.